Cartoons: Teaching solid waste separation in Elementary School I (Research, Society and Development, 2022)
The present text has the scope of exploring the potentialities that the use of media resources/animated cartoons has as a didactic tool, and its use with themes related to Environmental Education, in order to promote a critical science teaching. The approach is exploratory, in which two cartoons were selected on Youtube, one from Turma da Mônica and another from Show da Luna, for which, analyzed according to Content Analysis, three categories were created, being them: Environmental Discourse; Discourse of formation and orientation and Discourse of science, in order to explore the potential of cartoons to address the environmental theme in the early years of elementary school. It is noted that cartoons can be a strong didactic tool, because they draw the student's attention to the subject addressed, and the teacher can promote a contextualized and critical teaching.